2003
DOI: 10.1142/s0218625x03005232
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Orientation of Silver Films on Silicon Surfaces Revealed by Surface X-Ray Diffraction

Abstract: We have studied the crystal orientation of Ag thin films on a [Formula: see text] surface using grazing incidence X-ray diffraction with synchrotron radiation. After preparation of a [Formula: see text] surface, 50 ML Ag was deposited on the [Formula: see text] at the substrate temperature of 50–300 K. We found the [Formula: see text] structure at the interface. As for the Ag film, the Ag}111{ plane was mainly grown on the surface. The domain size of the Ag films strongly depends on the substrate temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…High-resolution scanning (inset of Figure a,b) supports the assignment of Ag(111) and Ag(100) orientations by the atomic arrangement. We also confirmed that √3 × √3 reconstruction remains at the interstitial regions between the islands, similar to previous findings , (Figure c).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…High-resolution scanning (inset of Figure a,b) supports the assignment of Ag(111) and Ag(100) orientations by the atomic arrangement. We also confirmed that √3 × √3 reconstruction remains at the interstitial regions between the islands, similar to previous findings , (Figure c).…”
Section: Resultssupporting
confidence: 93%
“…The growth of metals on semiconductors, such as the Ag/Si(111) system, has been the subject of much attention due to possible applications in nanoelectronics. Previous studies have focused on understanding the underlying physics that controls the epitaxial growth and formation of nanostructures. At room temperature, epitaxial growth of Ag on Si(111) follows a Stranski–Krastanov model where the formation of three-dimensional (3D) islands with varying heights occurs after the formation of a continuous film of 1 ML Ag. Previous studies have found that Ag islands grown on Si(111) have a Ag(111) preferred orientation, but depending on the temperature or coverage, nucleation of Ag(100) and Ag(110) islands may also be observed. , …”
Section: Introductionmentioning
confidence: 99%
“…34 Figure 9 shows a temperature dependence of domain sizes of surface twins estimated from FWHM's of diffuse scattering. This result may explain the small size of Ag crystals.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of the buried interfaces of several metal=semiconductor junctions were determined using surface X-ray diffraction (SXRD). Subsequently, long-range order (LRO) was reported to be maintained at the buried interfaces of Ag, [6][7][8][9][10] Pb, 11,12) and Bi 13) on the Si(111)7 × 7 substrate, and Ag 14) on the Si(111) ffiffiffi 3 p  ffiffiffi 3 p -Ag substrate. Scanning tunneling microscope (STM) images of the surfaces of ultra-thin Ag, 15) Pb, 16,17) and In 18) films on Si(111)7 × 7 substrates have also been reported to show 7 × 7 LRO at the interface.…”
Section: Introductionmentioning
confidence: 99%